Upaya Kantor Urusan Agama (KUA) Tenjolaya dalam Mengurangi Pernikahan Dini Kecamatan Tenjolaya - Maturidi (Ikatan Da'i Indonesia, 2024)
Early marriage is a social phenomenon that occurs in many regions in Indonesia. Generally, people perform early marriages due to several factors such as economic problems, low education, understanding of culture and certain religious values, and misuse of social media. This research was conducted at KUA Tenjolaya Bogor related to KUA's efforts to reduce early marriage, using qualitative field methods, using interviews, observation and documentation. The results of this study indicate that the factors of early marriage are not continuing education, promiscuity, family economy, parents / matchmaking The efforts made by the Tenjolaya KUA to reduce early marriage provide adequate education, empower the community to better understand the dangers of early marriage, increase the role of government and utilize its network, encourage the creation of gender equality, the importance of socializing sex education, carry out education through educational seminars on early marriage and Sakinah families, cooperate with the Indonesian Ulema Council Kec. Tenjolaya in marriage-related assistance, KUA Tenjolaya Go To School in cooperation with Forkopimcam Tenjolaya District.